2019
DOI: 10.31557/apjcb.2019.4.1.1-5
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ADP-ribose) Polymerase Promoter Hypermethylation Predispose Females to Breast Cancer

Abstract: Being the most common cause of female deaths worldwide, breast cancer (BC) is intensively studied over the last two decades. In the present investigation, we evaluated the promoter methylation of three cancer-related genes; PARP-1, p21, and Rb in 10 bi-matched BC samples (ductal carcinoma and lobular carcinoma) included the core tumor and the adjacent normal tissue. H&E-stained histopathological sectioning revealed grade 2 and grade 3 tumor cells. Methylation-specific PCR (MSP) was performed using methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, it was not the fact in a study on liver cancer, which demonstrated that non-cancerous liver tissues had a higher PARP1 expression level than the liver cancer tissues (Krupa et al, 2017). In addition, promoter hypermethylation of PARP1, which might be associated with lower expression level of PARP1, predisposed females to breast cancer (Sabit et al, 2019). Therefore, PARP1 might play distinct roles in different tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not the fact in a study on liver cancer, which demonstrated that non-cancerous liver tissues had a higher PARP1 expression level than the liver cancer tissues (Krupa et al, 2017). In addition, promoter hypermethylation of PARP1, which might be associated with lower expression level of PARP1, predisposed females to breast cancer (Sabit et al, 2019). Therefore, PARP1 might play distinct roles in different tumors.…”
Section: Introductionmentioning
confidence: 99%